2021
DOI: 10.3389/fonc.2021.700165
|View full text |Cite
|
Sign up to set email alerts
|

Could Camrelizumab Plus Chemotherapy Improve Clinical Outcomes in Advanced Malignancy? A Systematic Review and Network Meta-Analysis

Abstract: PurposeCamrelizumab is a novel programmed cell death 1 (PD-1) inhibitor. To determine the efficacy and safety of the combination treatment of camrelizumab+chemotherapy and camrelizumab monotherapy, and determine which is the most suitable malignancy type to be treated with camrelizumab, we performed a systematic review and network meta-analysis.MethodsWe searched PubMed, Embase, and the Cochrane Library for published clinical trials from database inception until April 2021. Studies that compared camrelizumab+c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Notably, the present study revealed that neoadjuvant camrelizumab plus PC chemotherapy achieved a better clinical response than neoadjuvant PC chemotherapy, and exhibited a higher ORR, CPR and MRP compared with those of neoadjuvant PC chemotherapy in patients with locally advanced NSCLC. A possible explanation could be that camrelizumab synergized with PC chemotherapy by blocking immune escape and enhancing chemosensitivity, therefore improving the neoadjuvant treatment response ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the present study revealed that neoadjuvant camrelizumab plus PC chemotherapy achieved a better clinical response than neoadjuvant PC chemotherapy, and exhibited a higher ORR, CPR and MRP compared with those of neoadjuvant PC chemotherapy in patients with locally advanced NSCLC. A possible explanation could be that camrelizumab synergized with PC chemotherapy by blocking immune escape and enhancing chemosensitivity, therefore improving the neoadjuvant treatment response ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the follow-up duration was relatively short, the present study revealed that neoadjuvant camrelizumab plus PC chemotherapy led to a 1-year DFS rate of 91.6% and a 1-year OS rate of 95.0% in patients with locally advanced NSCLC, which was in accordance with previous studies on other PD-1 inhibitors ( 31 , 32 ). Importantly, a control cohort was included in the current study, and it was observed that neoadjuvant camrelizumab plus PC chemotherapy led to a prolonged DFS time compared with that of neoadjuvant PC chemotherapy in patients with locally advanced NSCLC, with a benefit from the synergy between camrelizumab and chemotherapy ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For now, molecularly targeted drugs are still the main treatment strategy for advanced HCC (72)(73)(74). Among them, Sorafenib is the most widely used (75)(76)(77). In order to overcome the shortcomings of Sorafenib, newly molecular targeted drugs including Regorafenib, Lenvatinib and Cabozantinib have been approved for marketing one after another (78)(79)(80).…”
Section: Discussionmentioning
confidence: 99%
“…For each direct comparison for each outcome, we performed a random-effects pairwise meta-analysis to avoid inconsistencies caused by different studies. The heterogeneity among studies were assessed by p -value and I 2 statistics, and p -values <0.05 or I 2 >50% indicated heterogeneity in the outcome ( 20 ). For all dichotomous outcomes, the odds ratios (ORs) and corresponding 95% credible intervals (95%CIs) were used to confirm the significance of meta-analysis results, and for continuous outcomes, the standardized mean differences (SMDs) and their 95%CI were applied.…”
Section: Introductionmentioning
confidence: 99%